The Effectiveness of Online Learning Using E-Learning During Pandemic Covid-19 - Amin, Muhammad; Sibuea, Abdul Muin; Mustaqim, Bima (Universitas Pendidikan Ganesha, 2022)
Problems that often occur when online learning are, the material delivered by lecturers isn’t optimally taught due to lack of use good learning media. This study aims to find the effective use of online learning platforms in higher education. The research uses a qualitative approach, which aims to analyze, investigate and assess the effectiveness of online learning using e-learning in Indonesia during the Covid-19 pandemic. In addition, this study also compares which e-learning is easy to use, which has full-featured e-learning and which is economical. The subjects in this study were students enrolled in various universities in Indonesia with a total of 136 students. The method of data collection was done by distributing questionnaires via google forms to students. In this study, two analysis were used: descriptive analysis, and qualitative response analysis. The indicators used to see the effectiveness of e-learning are widely used, easy to use, full-featured, and economical. The most widely used e-learning in Indonesia are WhatsApp Group, Google Classroom, Ms. Teams, Schoology, Edmodo, and Moodle. From the results of the analysis it was found that the most effective e-learning used during a pandemic was Moodle. Because Moodle has complete and interesting features compared to other e-learning.